Laporan Keuangan Sebagai Penunjang Kinerja Forum UMKM Cikarang Pusat - Rina Nurjanah; Muhammad Mardi Putra Ilham; Citra Anisa Tika Putri; Cecep Ramdani (DPPM Universitas Pelita Bangsa, 2023)
The objective of this community service initiative is to support Micro, Small, and Medium Enterprises (MSMEs) affiliated with the MSME Forum in Central Cikarang District, Bekasi Regency. The forum encompasses a variety of businesses, such as culinary, handicrafts, fashion, and more. While some MSMEs have succeeded in growing their enterprises, many are still in the early stages. Due to limited knowledge and resources, these businesses have not been able to produce financial reports. Additionally, they lack an understanding of the importance of the information derived from financial reporting. Therefore, this community service project aims to address these issues by assisting in developing simple financial reports. These reports will serve as valuable tools for assessing business continuity, measuring success, making informed decisions regarding expansion, raising funds, and other strategic choices. The mentoring approach will be employed to guide and actively engage with MSMEs in the process of creating these straightforward financial reports for Central Cikarang MSME actors. The outcomes of the initiative revealed that participants gained an understanding of the components of financial reports through the training. However, they still require further support in comprehending the actual process of preparing these reports. Consequently, the project will be continued with the ultimate goal of enabling participants to independently generate financial reports.